Toll-like receptor 4 on stromal and hematopoietic cells mediates innate resistance to uropathogenic Escherichia coli - Schilling, Joel D. (The National Academy of Sciences, 2003)
Innate host defenses at mucosal surfaces are critical in the early stages of many bacterial infections. In addition to cells of the traditional innate immune system, epithelial cells can also produce inflammatory mediators during an infection. However, the role of the epithelium in innate host defense in vivo is unclear. Recent studies have shown that lipopolysaccharide (LPS) recognition is critical for bladder epithelial cells to recognize and respond to Escherichia coli. Moreover, the LPS-nonresponsive mouse strain C3H/HeJ, which has a mutation in the primary LPS receptor, Toll-like receptor 4 (TLR4), is extremely susceptible to infection with uropathogenic strains of E. coli. In this study, a bone marrow transplant approach was used to investigate the specific contributions of the bladder epithelium (and other stromal cells) in the TLR4-mediated innate immune response to the invading E. coli pathogen. Mice expressing the mutant TLR4 in the epithelial/stromal compartment were not able to mount a protective inflammatory response to control the early infection even when their hematopoietic cells expressed wild-type TLR4. However, the presence of TLR4(+) epithelial/stromal cells was not sufficient to activate an acute inflammatory response unless the hematopoietic cells were also TLR4(+). These results demonstrated that bladder epithelial cells play a critical role in TLR4-mediated innate immunity in vivo during a mucosal bacterial infection.